Blue moon - Lamangan, Joel.; Regal Entertainment (Pasig City Regal Entertainment, 2006)
At a quiet home in Boston, Massachusetts, an elderly Filipina named Corazon is writing a love letter knowing she does not have much time left. Corazon is writing to every man named Manuel Pineda who's listed in Philippine directory. Identifying herself as his long lost love. In the Philippines, an elderly man named Manuel Pineda is diagnosed with cancer and told he only has a few months to live Manuel decides that before he dies, he wants to find the woman he loved most, whom he hasn't seen in decades,Corazon. Such is the dramatic opening of emotional "Blue Moon" a hopeful moving love story that spans many decades.
VCD
Directed by Joel Lamangan.
Christopher De Leon, Dennis Trillo, Eddie Garcia, Boots Anson-Roa
Keywords: Feature films